Student-reported early-career STEM teachers’ classroom management, emotional engagement, and students’ interest in subject: a multilevel analysis: Student-reported early-career STEM teachers’ classroom management, emotional engagement, and students’ interest in subject: a multilevel analysis - Petrović, Dora; Pedić Duić, Paula; Pavin Ivanec, Tea (European journal of psychology of education, 2025)
The study examined the associations between perceived early-career teachers’ classroom management, emotional engagement, and students’ interest in STEM subjects. A total of 918 lower-secondary students rated classroom management and emotional engagement of their early-career STEM teachers ( N = 56) and their interest in the subject. Data was analysed using doubly latent multilevel modelling, exploring the mediation climate effect. As expected, in classes where the teacher is perceived as more efficient in managing the class, the teacher is also perceived as more emotionally engaged, whereas students in those classes experience higher interest in the subject. Surprisingly, the direct effect of perceived classroom management was not significant, indicating that the relationship between perceived teachers’ classroom management and class-level students’ interest in the subject might be (fully) explained by perceived teachers’ emotional engagement. The results highlight the importance of fostering self-efficacy and emotional engagement among early-career teachers to support and enhance students’ motivation in STEM subjects.